Regionalisation versus globalisation in European financial market integration: Evidence from co-integration analyses - Kleimeier, Stefanie; Sander, Harald (Journal of Banking & Finance, 2000)
Motivated by recent regulatory changes, this study investigates the degree of integration in retail lending in six core European Union (EU) countries using co-integration methodology which allows to investigate the presence and effects of structural breaks. While in the pre-break period we could detect integration to a limited degree, the evidence for integration weakened in the post-1992 period. This could however reflect a convergence process, particularly with respect to spreads. This result is clearly a regional, not a global phenomenon. As European lending rates are not yet fully integrated, the still segmented financial markets pose a challenge for a unified monetary policy.